2021
DOI: 10.1111/imj.14768
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin III as predictive indicator of survival in idiopathic pulmonary fibrosis (IPF) patients treated with nintedanib: a preliminary study

Abstract: Background: Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease often managed with nintedanib, a tyrosine kinase inhibitor targeting several profibrotic pathways. Although clotting processes are involved in wound healing and repair in the lung, there are no data on the role of antithrombin III (ATIII) in IPF patients treated with nintedanib. A previous proteomic analysis of serum of IPF patients before and after 1 year of nintedanib treatment showed differential protein expression of ATIII.Aims: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
8
2
Order By: Relevance
“…Indeed, in diabetic retinopathy, RAAS is an effector of vascular epithelial growth factor (VEGF) that drive the leakage of retinal blood vessels [ 50 ]. VEGF is also well known to be one of the major players in IPF onset and its receptor is one of the targets of nintedanib treatment [ 11 , 51 ].…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in diabetic retinopathy, RAAS is an effector of vascular epithelial growth factor (VEGF) that drive the leakage of retinal blood vessels [ 50 ]. VEGF is also well known to be one of the major players in IPF onset and its receptor is one of the targets of nintedanib treatment [ 11 , 51 ].…”
Section: Metabolic Alterations In Ipfmentioning
confidence: 99%
“…There is an urgent need for reliable biomarkers for early diagnosis and to monitor progression. Recent studies have identified potentially useful peripheral and bronchoalveolar lavage (BAL) biomarkers, including chemokines, cytokines, genes and proteins [ 10 , 11 , 12 , 13 , 14 , 15 ], but the 2018 International Guidelines for the Clinical Diagnosis of IPF do not include recommendations, due to insufficient evidence [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our proteomic analysis also highlighted the abundance of antithrombin III in serum after one year of nintedanib treatment 28 . This protein is one of the most important serine protease inhibitor in plasma where it regulates the clotting cascade by inhibiting thrombin, matriptase-3/TMPRSS7, and clotting factors IXa, Xa and XIa.…”
Section: Discussionmentioning
confidence: 73%
“…Transient activation of platelets induces pro-inflammatory and pro-fibrotic effects [ 42 ]. While the role of platelets in IPF is unknown [ 43 , 44 ], platelet trapping in the lungs of mice following intravenous bleomycin administration showed a strong correlation with subsequent collagen deposition, suggesting a role in fibrogenesis in this animal model [ 42 ].…”
Section: Discussionmentioning
confidence: 99%